2010
DOI: 10.1111/j.1440-1797.2010.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of percutaneous renal biopsy in chronic kidney disease

Abstract: After more prolonged elevations of S-cr, PRB may be less safe and less likely to reveal treatable disease and opportunities for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Percutaneous kidney biopsy is currently the definitive diagnostic method for determining CKD etiology. Although the occurrence of complications is relatively low, the invasive nature of kidney biopsy has inherent risks which may rule out the use of the procedure with some patients such as those with compounding medical conditions [4][6]. Cost and access to care are also considerations for the use of renal biopsy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous kidney biopsy is currently the definitive diagnostic method for determining CKD etiology. Although the occurrence of complications is relatively low, the invasive nature of kidney biopsy has inherent risks which may rule out the use of the procedure with some patients such as those with compounding medical conditions [4][6]. Cost and access to care are also considerations for the use of renal biopsy [4].…”
Section: Introductionmentioning
confidence: 99%
“…These subjects may have a higher risk of bleeding and have lower chances of diagnostic success, particularly when the kidneys are smaller and more scarred [94] . Nevertheless, renal biopsy in CKD patients is relatively a safe procedure as reported in several studies [94][95][96][97][98][99] and may represent a valid tool for clinical management.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…These subjects may have a higher risk of bleeding and have lower chances of diagnostic success, particularly when the kidneys are smaller and more scarred [94] . Nevertheless, renal biopsy in CKD patients is relatively a safe procedure as reported in several studies [94][95][96][97][98][99] and may represent a valid tool for clinical management. Renal tissue obtained by biopsy cannot give a great quantity of information if chronic damage (tubulointerstitial fibrosis, glomerulosclerosis, arteriosclerosis) prevails [8] and there is usually an inverse relationship between the degree of renal function and the need for therapeutic changes [94] .…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Patient related factors include age >40 years, female gender, elevated serum creatinine and lower haemoglobin level at the time of the procedure. 5 , 9 , 10 The main procedure related factor was the use of 14G needles. It was observed that the increased number of passes due to the use of smaller diameter needles did not lead to increased haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%